Measuring what is top of mind - Ingar Haaland; Christopher Roth; Stefanie Stantcheva; Johannes Wohlfart (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
We survey the recent literature in economics measuring what is on top of people's minds using open-ended questions. We first provide an overview of studies in political economy, macroeconomics, finance, labor economics, and behavioral economics that have employed such measurement. We next describe different ways of measuring the considerations that are on top of people's minds. We also provide an overview of methods to annotate and analyze such data. Next, we discuss different types of applications, including the measurement of motives, mental models, narratives, attention, information transmission, and recall. Our review highlights the potential of using open-ended questions to gain a deeper understanding of mechanisms underlying observed choices and expectations.
Keywords: C90; D83; D91; 330; Thoughts; Open-ended Questions; Text Data; Methodology; Surveys; Qualitative Research